Salt pan and salt playa extents in western United States based on Landsat-8 imagery - Samira Safaee; Jida Wang (PANGAEA, 2020)
This dataset provides a static extent of salt pans and salt playas (a total area of ~10 thousand km^2) across the arid/semiarid western United States (US). The considered region (an area of ~700 thousand km^2), also given in this dataset, includes the endorheic (i.e., hydrologically landlocked) areas in the Great Basin, the Mojave Desert, the north part of the Chihuahua Desert, and other sporadic endorheic basins in the western US, with a small fraction extending to northern Mexico (see Figure 2 in Safaee and Wang (2020) for the area boundary). The salt pan/playa extents were mapped using a calibrated support vector machine (SVM) from the 30-m-resolution multispectral Landsat-8 Operational Land Imager (OLI) images that were acquired in June during 2013 to 2015. The mapping result may represent the maximum salt pan/playa condition during this three-year period. In addition, this dataset also provides the OLI-based training pool that was used by the SVM to perform the binary classification between salt-covered surface and others (soil and barren land). This training pool was generated using a stratified sampling method which randomly selected an equal number of pixels from each of the eight training sites worldwide, for both salt and non-salt regions. A total of 8000 sampling points (4000 for salt and 4000 for non-salt) are included in the sample pool. Refer to Safaee and Wang (2020) for more technical details. Please also see Data_description (within zip file, or see "Further details").